Fiber concentrates from raspberry and blueberry pomace in gluten‐free cookie formulation: Effect on dough rheology and cookie baking properties. Issue 2 (14th November 2018) - Šarić, Bojana; Dapčević‐Hadnađev, Tamara; Hadnađev, Miroslav; Sakač, Marijana; Mandić, Anamarija; Mišan, Aleksandra; Škrobot, Dubravka
Abstract: Raspberry and blueberry pomace, by‐products from fruit juice industry, were dehydrated to obtain fruit fiber concentrates and valorized as ingredients in gluten‐free (GF) cookies formulation. The aim was to evaluate the effect of substituting 30% (w/w) of GF flour mixture with different ratios of blueberry/raspberry fiber concentrates (0/30, 15/15, and 30/0) on rheological properties of cookie dough and cookie baking quality. Generally, the incorporation of the fiber concentrates increased the elastic and the viscous moduli thus producing harder doughs and consequently firmer cookies in comparison to the control. Although having similar total, soluble and insoluble fiber content, blueberry fiber concentrates were characterized with higher water absorption capacity and consequently yielded cookies with more rigid dough structure, higher water loss during baking, lower cookie thickness, higher spread ratio, more dense inner structure, and increased cookie hardness than those containing raspberry fiber concentrates. Enrichment of GF cookies with raspberry and blueberry fiber concentrates resulted in products with dietary fiber content higher than 6 g per 100 g, thus making them candidates for bearing "high fiber" nutrition claim. Practical applications: Currently available GF bakery products mostly lack dietary fibers (DFs) and other important nutrients, because they are usually manufactured from refined flour and/or starches. As the products with long shelf‐life, very popular in daily diet of almost all consumer profiles, cookies could represent good matrices for the addition of functional ingredients, such as DFs. In this paper, GF cookies were enriched with the fiber concentrates recovered from blueberry and raspberry pomace. Application of these fiber sources enabled recycling of fruit processing industry by‐products into novel, "high fiber" GF product with improved nutritive profile.